2016
DOI: 10.3390/ijms17020186
|View full text |Cite
|
Sign up to set email alerts
|

Liensinine- and Neferine-Induced Cardiotoxicity in Primary Neonatal Rat Cardiomyocytes and Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: Due to drug-induced potential congestive heart failure and irreversible dilated cardiomyopathies, preclinical evaluation of cardiac dysfunction is important to assess the safety of traditional or novel treatments. The embryos of Nelumbo nucifera Gaertner seeds are a homology of traditional Chinese medicine and food. In this study, we applied the real time cellular analysis (RTCA) Cardio system, which can real-time monitor the contractility of cardiomyocytes (CMs), to evaluate drug safety in rat neonatal CMs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Unlike primary rat neonatal cardiomyocytes, the beating activity of hiPS-CMs is more stable and is barely influenced by the seeding density of hiPS-CMs or medium changing. Therefore, hiPS-CMs have gained wide acceptance as a biologically relevant in vitro model for drug discovery and cardiotoxicity screens [21, 22]. Compared to cytotoxicity assays on H9C2 cell line, hiPS-CMs are more sensitive for the detection of potential cardiac side effects which can be indicated by the beating patterns of CMs [23].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike primary rat neonatal cardiomyocytes, the beating activity of hiPS-CMs is more stable and is barely influenced by the seeding density of hiPS-CMs or medium changing. Therefore, hiPS-CMs have gained wide acceptance as a biologically relevant in vitro model for drug discovery and cardiotoxicity screens [21, 22]. Compared to cytotoxicity assays on H9C2 cell line, hiPS-CMs are more sensitive for the detection of potential cardiac side effects which can be indicated by the beating patterns of CMs [23].…”
Section: Introductionmentioning
confidence: 99%
“…From above in vitro studies, a reasonable interpretation of the observed in vivo cardiotoxicity could not be reached and more studies are still needed. Interestingly, Neferine, one of the four natural products we used to extract the chemical scaffold in this paper, was reported to possess potential cardiotoxicity by disruption of calcium homeostasis 52 . In our case, compound 6a-1 downregulated the calcium overload in corticorsterone-injured PC12 cells.…”
Section: Resultsmentioning
confidence: 98%
“…The development of drug evaluation systems remains difficult due to the lack of human cardiomyocyte models and suitable methods. HiPSC-CMs, which have predefined contractile characteristics of native cardiomyocytes, a genetically relevant background and the scope of serving as a model of relevant cardiac disease phenotypes, have provided an opportunity for pre-clinical drug evaluation ( 14 , 24 ). More importantly, hiPSC-CMs also have stable electrophysiological and contractile characteristics, which allows for a wide range of applications, including drug discovery, toxicity testing and cardiac disease research ( 12 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The RTCA Cardio system allows for the real-time, label-free and non-invasive analysis of cardiomyocyte function. This platform has been used for cardiovascular toxicity screening, drug-induced cardiac contractility evaluation and estimating the risk of drug-induced arrhythmia ( 14 – 17 ).…”
Section: Introductionmentioning
confidence: 99%